Customer Satisfaction in Public Sector Banks of Tamilnadu With Reference to Erode District - Sundharesalingam, P; Umasankar, M (Journal of Commerce and Trade, 2015)
The Private sector banks in India have achieved a higher growth rate compared with Public sector banks over a seven year period (2004~2011). Data is collected through a questionnaire from 975 customers at 41 branches of 5 public sector banks and private sector banks each, located in the 5 taluks of Erode district. Data on Bank/Branch attributes, Customer Service Characteristics, Customer attributes, Perception about Competitors, the period of holding the account, the reason for choosing a particular bank, the likely period for which the customer will maintain the account and the likely reason for changing the bank were collected and analysed. Logistic regression model is used to identify the factors that contributed to Customer Satisfaction. The study finds that Bank/ Branch attributes such as convenient location, access, and parking space and working hours have the greatest impact on Customer Satisfaction. Customer service characteristics like account handling, customer friendly policies and customer handling also influence Customer Satisfaction. However, Customer satisfaction itself does not have an effect on the length of period the customer will continue to maintain his account. The most important reason why customers intend to change the bank is “Change in job/ residence” followed by the “Need for more facilities (credit)”. “Customer service” is given as a reason for leaving only over a longer period of 1 to 5 years.